2020
DOI: 10.3390/ma13122711
|View full text |Cite
|
Sign up to set email alerts
|

Melt Conditioned Direct Chill (MC-DC) Casting and Extrusion of AA5754 Aluminium Alloy Formulated from Recycled Taint Tabor Scrap

Abstract: The melt conditioned direct chill (MC-DC) casting process has been used to produce billets and extruded planks of AA5754 alloy formulated from 100% recycled Taint Tabor scrap aluminum. The billets were homogenized and then extruded into flat planks. Optical metallography of the MC-DC cast billets showed equiaxed refined grains in comparison to conventional direct chill (DC) cast and direct chill grain refined (DC-GR) cast billets formulated from the same Taint Tabor scrap. Microstructural evaluation of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… Schematic diagram of the melt conditioned direct chill casting (MC-DC) with the rotor-stator shearing device submerged in the sump of a conventional DC casting mold [ 1 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… Schematic diagram of the melt conditioned direct chill casting (MC-DC) with the rotor-stator shearing device submerged in the sump of a conventional DC casting mold [ 1 ]. …”
Section: Figurementioning
confidence: 99%
“…The challenge for aluminum production is to cut 50% of CO 2 emission by 2050. Re-melting of end-of-life aluminum scrap consumes 5% of the energy required to produce primary aluminum and can saves up to 95% of CO 2 emission [ 1 , 2 ]. In the UK, the main motivation for recycling is the provision of aluminum automotive body-sheet and structural castings from a sustainable end-of-life scrap source for the mass manufacture of lightweight low embedded carbon vehicle bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatic et al [9] numerically studied the impact of changing the inlet geometry on macro-segregation, the flow of melt, the temperature of billet and solid fraction for the production of Al-Cu alloy billet with 240 mm diameter using a direct chill casting technique. Al-Helal et al [10] reported an enhancement in the mechanical properties of planks produced by melt conditioned type direct chill casting process in comparison to direct chill casting. The study reported 1.2% improvement in ultimate tensile strength and an increase in elongation by 5.8%.…”
Section: Introductionmentioning
confidence: 99%